Адаптація вартісно-орієнтованого управління підприємством до об’єктів житлової нерухомості - Бабак, Альона Валеріївна (КНУБА, 2021)
У першому розділі досліджено сегмент житла, зайнятого власниками у багатоквартирних будинках, організацію управління будинками, показано внесок авторки у теорію і практику організації управління об’єктами власності і житлово-комунальними послугами мешканцям.Методологічною основоюподальшого дослідження економічних проблем власників було обрано підходи вартісно-орієнтованого управління підприємствами в інтересах акціонерів з їхньою адаптацією до багатоквартирного будинку.У другому розділі проаналізовані типові моделіспільної власності на житло, поширені за кордоном іпоказано, що у вітчизняній дуалістичній моделі відсутня належна увага до будинку як основного об’єктавитрат і вартості. Показано недоліки кошторисного ціноутворенні робіт, що неприйнятно для управління витратами елементами будинку. Обґрунтовано відповідну трансформацію кошторисної вартості.Удосконалено відображення витрат в обліку забудовників і власників об’єктів нерухомості (управителів).Запропонованометод визначення вартості життєвого циклу багатоквартирного будинку і повних витрат власників квартир. Обраховано річну вартість власності на житло, яка з урахуванням інвестиційної складової значно перевищує вітчизняні статистичні показники. У завершальному розділі роботи показано особливості організації ринку житлово-комунальних послуг за різними моделями відносин між мешканцями (власниками) і виконавцями. Доведено переваги моделі відносин «будинок – виконавці житловокомунальних послуг». The dissertation is generallydevoted to improving the value management of an apartment building as a common property of apartment owners. The first section shows the unsatisfactory technical condition of multi-apartment housing in Ukraine in connection with the privatization of apartments by residents. This requires the implementation of the necessary costs for the maintenance and operation of land and buildings, the ability of the owners to bear these costs. There are a number of unresolved issues that relate to the valuation of property - both regulated by law and 21 used in management practice. The main one is the issue of determining the value and value management of the house, which is co-owned by the owners (residents) of apartments, because proper maintenance and repair of the house affect its condition and determine the duration, quality and cost of living in it. Thus, the main objects of management are houses (with land plots), not apartments and other non-residential premises. To solve the existing management problems in relation to the house, methods of estimating the cost of the life cycle over the period of construction and operation were analyzed, selected and applied with the possibility of detailing by stages of change of owners and years of operation. In addition, methodological approaches to costoriented management of enterprises in the interests of shareholders with their adaptation to the house as an object of joint ownership were chosen. as well as micro-level management methods. In the second section, using the method of international comparisons, the management of property in an apartment building was considered in the context of the advantages and disadvantages of typical models of property common abroad. It has been shown that the domestic model has created a lack of proper attention to the house as the main object of value, which has distorted all derivative property relations and economic processes. Based on the systematization of costs, regardless of the model, an algorithm for determining the value of the life cycle of an apartment building for owners was proposed. Further detailed studies of cost formation at the design and construction stage showed the shortcomings of structuring the value of the house in the estimated pricing by cost of work, which is unacceptable for further cost management in the house by its cost and benefit centers - structural and spatial elements. The corresponding transformation of the estimated cost was methodically substantiated and practically carried out.At the stage of the sale of apartments, the reflection of the value in the accounting of developers and owners of real estate (managers) was studied. It was shown that when a developer sells apartments as separate real estate, the value of the house in accounting seems to dissolve, which formally removes it from the management of value according to accounting data. It was proposed to introduce of the necessary management accounting in apartment buildings for various purposes (investment, income, cooperative). In continuation of the estimated structuring of the cost, management accounting is provided for structural elements and apartments and nonresidential premises. Based on the classification of life cycle costs and on the basis of a combination of domestic and European statistics, the annual cost of home ownership was determined, which, taking into account the investment component, significantly exceeds the current statistical level. The final section of the work showed the place of the house and its owners as consumers in the market of housing and communal services in Ukraine. The peculiarities of the market organization according to different models of relations between residents (owners) and executors of housing and communal services were shown. The advantages of the model of relations "house - contractors of housing and communal services" were proved. At the end of the section the author's concrete contribution to the improvement of the regulation of the markets of services of communal enterprises of water supply and sewerage, district heating was shown.
Adaptation of enterprise cost-oriented managementto housing property
Keywords: життєвий цикл; витрати; відносини; будинок; квартира; ціноутворення; облік; підприємство; житлово-комунальні послуги; life cycle; costs; relations; house; apartment; pricing; accounting; enterprise; housing and communal services; 69.003:658.014